KELAYAKAN AGROINDUSTRI KOPI LUWAK DI KABUPATEN LAMPUNG BARAT - Febrianti, Febrianti; Utomo, Tanto Pratondo; Nugraha, Adia (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2011)
West Lampung is one of coffee production center in Lampung. Some farmers have began to ferment their coffee bean biologically using Luwak .This project was aimed to study whether the establishment of ‘Luwak’ coffee industry at West Lampung will bring benefit to farmers. The result of the study shows that the market for ‘LUWAK’ coffee is very potential because the plantation/production area at West Lampung is widely available. By using CAMCE China technology it can be estimated that the total production of 3200 kg per year will be achieved. CAMCE was chosen because it uses latest technology, needs lower investing cost in equipment , and offers a complete factory construction. In addition there are plenty of human resources available to be involved in establishing this industry.